Abattoir surveillance of Sarcocystis spp., Cysticercosis ovis and Echinococcus granulosus in Tasmanian slaughter sheep, 2007–2013. Issue 3 (26th February 2018) - Phythian, CJ; Jackson, B; Bell, R; Citer, L; Barwell, R; Windsor, PA
Abstract : Objective: To estimate the prevalence of macroscopic Sarcocystis spp., Cysticercus ovis and Echinococcus granulosus recorded at routine postmortem inspection of Tasmanian slaughter sheep during 2007 to 2013. Methods: A retrospective analysis of routine postmortem meat inspection data maintained on 352, 325 Tasmanian adult slaughter sheep inspected across nine abattoirs in Tasmania, Victoria and South Australia as part of the National Sheep Health Monitoring Project (NSHMP). Results: During the period 1 September 2007 to 30 June 2013, the estimated prevalence of macroscopic Sarcocystis spp. was 14.3%, C. ovis was 3.2% and E. granulosus was 0.01%. Mean Sarcocystis spp. line prevalence ranged from 0% to 33.5%. Significant between‐abattoir differences in the level of sarcosporidiosis (P < 0.001) and C. ovis were found (P < 0.001). Overall, very low levels of hydatidosis were recorded throughout the surveillance period. Predicted within‐line prevalence of macroscopic sarcocysts in animals coming from a known/recorded local government area (LGA) (P < 0.001) was lower than that of lines where the LGA was unknown or not recorded. A higher prevalence of sarcocystosis was recorded in lines of sheep aged ≥ 2 years compared with those < 2 years (P < 0.001). Conclusion: Reasons for the significant between‐abattoir differences in recorded levels of ovine sarcosporidiosis and cysticercosis remain unknown, but may represent sampling bias, with subsets of slaughter sheep going to abattoirs with different tiers or access to markets. Further investigation into apparent differences, including epidemiological studies of properties with high lesion prevalence, comparing meat inspector diagnostic sensitivity, assessing the effect of line speed and tiers and market access in different abattoirs, may be useful.